The Empty Breadbasket_ When the land that feeds the nation cannot feed itself - Hallaq, Tom, G.; Punnett, Case Ian (KTWU-TV, 2021)
The Empty Breadbasket: When the land that feeds the nation cannot feed itself is a documentary addressing food deserts in rural Kansas. The documentary features Dr. David Procter, Professor Emeritus at Kansas State University, and several students from the A.Q. Miller School of Media and Communication. Dr. Procter co-founded the Rural Grocery Initiative to identify challenges faced by rural grocery stores. The documentary premiered on the KSU campus December 13, 2021 and aired on KTWU (PBS), Topeka, KS and RFD-TV, Nashville, TN in early 2022. Recognized as a Silver winner in the 2022 Telly Awards.
The Empty Breadbasket
Keywords: Food Deserts; Food access; Rural; Kansas; Documentary